Guideline for Salinity Assessment, Mitigation and Adaptation Using Nuclear and Related Techniques - Zaman, Mohammad (Springer International Publishing, 2018)
This open access book is an outcome of the collaboration between the Soil and Water Management & Crop Nutrition Section, Joint FAO/IAEA Division of Nuclear Techniques in Food and Agriculture, Department of Nuclear Sciences and Applications, International Atomic Energy Agency (IAEA), Vienna, Austria, and the International Center for Biosaline Agriculture (ICBA), Dubai, UAE. The objective of this book is to develop protocols for salinity and sodicity assessment and develop mitigation and adaptation measures to use saline and sodic soils sustainably. The focus is on important issues related to salinity and sodicity and to describe these in an easy and user friendly way. The information has been compiled from the latest published literature and from the authors' publications specific to the subject matter. The book consists of six chapters. Chapter 1 introduces the terms salinity and sodicity and describes various salinity classification systems commonly used around the world. Chapter 2 reviews global distribution of salinization and socioeconomic aspects related to salinity and crop production. Chapters 3 covers comprehensively salinity and sodicity adaptation and mitigation options including physical, chemical, hydrological and biological methods. Chapter 4 discusses the efforts that have been made to demonstrate the development of soil salinity zones under different irrigation systems. Chapter 5 discusses the quality of irrigation water, boron toxicity and relative tolerance to boron, the effects of chlorides on crops. Chapter 6 introduces the role of nuclear techniques in saline agriculture.